An Experimental Investigation on the Effects of Nanofluid and Peltier Element on Diesel and Biodiesel Blends in Compression Ignition Engine - Manimaran, R; Murugu Mohan Kumar, K (International Journal of Engineering and Technology, 2018)
This research work discusses the experimental investigations on the combined effects of Nanofluid and Peltier elements in mahua biodiesel blends with diesel fuel.Â The fuel test was carried out in a single cylinder ata constant speed (1500 rpm) direct injection diesel engine. Mahua oil used as an effective alternative to diesel fuel and mahua methyl ester derived from transesterification process. The mahua biodiesel was blended with diesel and nanofluid on volume fraction like M10, M20, M10* and M20*. Nanofluidin biodiesel blends with diesel resultsefficient combustion leads to improvement in engine performance, butit causes an increase in viscosity. Peltier element was used to reduce biodiesel blend viscosity with the principle of thermo-electricity.Finally, this research work concludes Mahua biodiesel 20% + diesel 80% + 2ml of aluminium oxide nanofluid (M20*) fuel act as an effective alternative fuel.M20*blend results in better engine combustion, performance (improved BTE and optimum BSEC) and decreased emission ofÂ NOx, Smoke and increased HC, CO emissions as compared to diesel fuel operation at peak power outputs.Â Â